2019
DOI: 10.1016/j.jpedsurg.2019.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for the treatment of sacrococcygeal pilonidal sinus disease in children: A systematic review and meta-analysis

Abstract: BackgroundPilonidal sinus disease (PNS) is not uncommon in children. Controversy remains over the best treatment and there is limited evidence. This systematic review and meta-analysis aims to establish which techniques have the best outcomes in children. MethodsMEDLINE, EMBASE and CENTRAL databases were searched. Studies reporting treatment outcomes for PNS in children were included. ResultsOpen healing has pooled risk of recurrence of 26% (95%CI 15-38%), risk of wound complication of 21% (9-36%) and wound he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
(70 reference statements)
0
31
2
Order By: Relevance
“…Recurrence rates are 11-42% in adults and 12% (8-25%) in children. 4,15,16 In contrast, we observed 40% and 28% recurrence (7% needed a re-operation), respectivelyvalues that are higher than in literature reports. Overall, there is general consensus amongst some level 1 studies and multiple systematic reviews, that midline closure is inferior to any type of off-midline closure (including flaps) in terms of infection, healing time, wound dehiscence, and possibly recurrence rates.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Recurrence rates are 11-42% in adults and 12% (8-25%) in children. 4,15,16 In contrast, we observed 40% and 28% recurrence (7% needed a re-operation), respectivelyvalues that are higher than in literature reports. Overall, there is general consensus amongst some level 1 studies and multiple systematic reviews, that midline closure is inferior to any type of off-midline closure (including flaps) in terms of infection, healing time, wound dehiscence, and possibly recurrence rates.…”
Section: Discussioncontrasting
confidence: 82%
“…symptoms and presenting at the hospital was 6 AE 2.35 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) months.…”
Section: Resultsmentioning
confidence: 99%
“…However, recurrence and complication are not the only determinants of SPS treatment. In particular, the factors affecting the quality of life such as school attendance, sportive activities and socialization in the adolescent age group should not be ignored when appropriate treatment is selected (6) . In our study, no significant difference was observed between MEPC and LF met-hods in the recovery time and patient satisfaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, procedures commonly used in the treatment of SPS are either to leave the wound to secondary healing after extensive excision of SPS or to close the wound with flap or without flap (5) . However, each of these procedures has its own advantages and disadvantages (6) . For example, wounds left for secondary healing recover much later than primary closure wounds, but relapse rates are lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation